Informative Value of Non-Financial Reports: Analyzing the Impact of Disclosure Format and Auditing - Simon Hirsch; Veronika Heichl (Journal of Corporate Accounting & Finance, 2025)
Since the Non-Financial Reporting Directive (NFRD) came into force in 2017, large, listed companies in the European Union (EU) are obliged to disclose non-financial reports annually. Accordingly, Member States transposed the Directive into national law with country-specific rules. Thus far, quantifying the informational content has proven to be difficult. Therefore, we applied an innovative text-mining approach to assess the informative value of non-financial reports and its influential determinants, the so-called Sustainable Fingerprint. This method measures how precisely environmental, social, and governance (ESG) topics and time references are disclosed in non-financial reports. The aim of our paper is to analyze the informative value of non-financial reports from companies in the main stock indices of France, Germany, Italy, and Sweden after the national NFRD implementation. Our results show that incorporating the non-financial report in the annual report and the audit committee expertise (ACE) are positively related to the informative value, whereas external assurance has no significant impact.
Keywords: 650; ESG; NFRD; non-financial reporting; sustainability disclosure; textual analysis